Adaptation of Arabidopsis halleri to extreme metal pollution through limited metal accumulation involves changes in cell wall composition and metal homeostasis. Issue 2 (6th February 2021) - Corso, Massimiliano; An, Xinhui; Jones, Catherine Yvonne; Gonzalez‐Doblas, Verónica; Schvartzman, M. Sol; Malkowski, Eugeniusz; Willats, William G. T.; Hanikenne, Marc; Verbruggen, Nathalie
Summary: Metallophytes constitute powerful models for the study of metal homeostasis, adaptation to extreme environments and the evolution of naturally selected traits. Arabidopsis halleri is a pseudometallophyte which shows constitutive zinc/cadmium (Zn/Cd) tolerance and Zn hyperaccumulation but high intraspecific variability in Cd accumulation. To examine the molecular basis of the variation in metal tolerance and accumulation, ionome, transcriptome and cell wall glycan array profiles were compared in two genetically close A. halleri populations from metalliferous and nonmetalliferous sites in Northern Italy. The metallicolous population displayed increased tolerance to and reduced hyperaccumulation of Zn, and limited accumulation of Cd, as well as altered metal homeostasis, compared to the nonmetallicolous population. This correlated well with the differential expression of transporter genes involved in trace metal entry and in Cd/Zn vacuolar sequestration in roots. Many cell wall‐related genes were also more highly expressed in roots of the metallicolous population. Glycan array and histological staining analyses demonstrated that there were major differences between the two populations in terms of the accumulation of specific root pectin and hemicellulose epitopes. Our results support the idea that both specific cell wall components and regulation of transporter genes play a role in limiting accumulation of metals in A. halleri at contaminated sites.